Developing a Culture of Readers: Complementary Materials That Engage. (2nd May 2017) - Sailors, Misty; Kaambankadzanja, Davie
Abstract: Many professionals, including members of the International Literacy Association, are concerned with the lack of reading materials in classrooms across the world. In this paper, the authors present the creation of high‐quality, locally produced, complementary reading materials in Malawi, where there are very few children's books and few opportunities to read extended texts. The authors describe their approach to the creation of those materials, using engagement as their theoretical frame. Because many teachers in countries such as Malawi (and in many schools in the United States) often receive books that are culturally and linguistically inappropriate, the authors argue for the importance of local reading materials that take engagement into consideration as teachers make decisions about the reading materials they use in their classrooms.